2020
DOI: 10.3892/ijo.2020.5120
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of canagliflozin on pancreatic cancer are mediated via the downregulation of glucose transporter‑1 and lactate dehydrogenase A

Abstract: Pancreatic cancer is one of the most lethal solid malignancies, with a poor prognosis and a high mortality rate. Pancreatic cancer cells exhibit enhanced glycolysis to maintain their rapid growth. Canagliflozin (CANA) is a sodium-glucose co-transporter 2 inhibitor used for the clinical treatment of diabetes. Recent studies have demonstrated the potential ability of CANA to suppress hepatocellular carcinoma, whereas its therapeutic effects on and mechanisms in pancreatic cancer have rarely been reported. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Particularly, recent evidence has highlighted the inhibitory effects of several SGLT2 inhibitors on tumors. Xu et al [13] demonstrated that CANA could reduce cell viability and increase apoptotic rate in pancreatic cancer. Dapagliflozin, another SGLT2 inhibitor, could inhibit tumor growth and cancer proliferation by targeting the adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) pathway [14].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, recent evidence has highlighted the inhibitory effects of several SGLT2 inhibitors on tumors. Xu et al [13] demonstrated that CANA could reduce cell viability and increase apoptotic rate in pancreatic cancer. Dapagliflozin, another SGLT2 inhibitor, could inhibit tumor growth and cancer proliferation by targeting the adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) pathway [14].…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic cancer, the PI3K/Akt signaling pathway also functions as an antitumor drug target. Xu et al [ 40 ] found that canagliflozin exerted antitumor effects by inhibiting glycolysis through the PI3K/Akt/mTOR signaling pathway, which was improved when combined with gemcitabine, revealing the potential of this pathway in the clinical treatment of pancreatic cancer. However, previous studies investigating the antitumor mechanism of scoparone were insufficient and ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…A cell study in breast cancer proved that SGLT-2 inhibitors could reduce the viability of breast cancer cells by inducing G1 phase arrest and apoptosis based on the adenosine-monophosphate activated protein kinase/mammalian target of rapamycin (AMPK/mTOR) signal pathway [116] . Other evidence indicated that SGLT-2 could also inhibit the proliferation of cancer cells in lung cancer [117] and pancreatic cancer [118] .…”
Section: Repositioning Potential Of Antidiabetic Drugsmentioning
confidence: 99%